Optimization of synthesis and application processes for composite crosslinked chitosan derivatives fly ash for removal of Reactive Red 120 dye / Ibrahim Awad Mohammed - Mohammed, Ibrahim Awad (2023)
Recently, many researchers have been focused on enhancing chitosan by using a physicochemical modification for enhancing the surface structure of chitosan and improving its chemical stability in an acidic environment. In this research work, the adsorption of Reactive Red 120 (RR120) in an aqueous solution onto three biocomposite adsorbents was highlighted. These adsorbents were prepared by loading chitosan with different ratios of Fly Ash (FA) and crosslinking using three different organic crosslinking agents namely: Tripolyphosphate (TPP), Ethylene Glycol Diglycidyl Ether (EDGE), and Epichlorohydrin (ECH). Box–Behnken design (BBD) was applied to optimize five experimental parameters including FA loading ratio (A: 050%), adsorbent dose (B: 0.02–0.1 g/100mL), solution pH (C: 4–10), temperature (D: 30 °C–60 °C), and time (E: 20–90 min). Experimental data were analyzed using Langmuir, Freundlich and Temkin isotherm models to evaluate the maximum adsorption capacities of the adsorbents. The composites were characterized using pH point of zero charge (pHPZC), pH-potentiometric titration, elemental analysis, scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, energydispersive X-ray (EDX) spectroscopic techniques and BET surface analysis. The BET surface area of the three adsorbents showed significant increase after the loading of FA particles which improve the accessibility of active adsorption sites for the dye molecules and consequently aid the dye adsorption process.